Assessing the Implications of Allowing Transgender Personnel to Serve Openly - Schaefer, Agnes Gereben (RAND Corporation, 2016)
The U.S. Department of Defense is considering a change in policy to allow transgender military personnel to serve openly. A RAND study examined the health care needs of transgender personnel, the costs of gender transition-related care, and the potential readiness implications of a policy change. The experiences of foreign militaries that permit transgender service members to serve openly also point to some best practices for U.S. policymakers.